Nigeria National Policies and Strategies (NPS) and Foresight and Metrics (F&M) Initiative's Capacity Sharing Workshops Series: Bui - Onilogbo, Omobolanle (International Food Policy Research Institute, 2023)
On September 5, 2022, the International Food Policy Research Institute (IFPRI) kicked off a four-day “Building a Nigerian Social Accounting Matrices (SAM)” training as part of a series of Nigeria Capacity Sharing Workshops Series under the CGIAR National Policies and Strategies for Food, Land and Water Systems Transformation (NPS) Initiative, and Foresight &Metrics initiative.